A pilot study evaluating the effects of prestorage leukoreduction on markers of inflammation in critically ill dogs receiving a blood transfusion. Issue 4 (20th June 2019) - Bosch Lozano, Luis; Blois, Shauna L.; Wood, R. Darren; Abrams‐Ogg, Anthony C. G.; Bersenas, Alexa M.; Bateman, Shane W.; Richardson, Danielle M.
Abstract: Objectives: To compare markers of inflammation after transfusion of leukoreduced (LR) packed RBCs (pRBCs) versus non‐LR pRBCs in dogs with critical illness requiring blood transfusion, and to report survival to discharge and rates of transfusion reactions in these dogs. Design: Prospective randomized blinded clinical study June 2014–September 2015. Setting: University veterinary teaching hospital. Animals: Twenty‐three client‐owned critically ill dogs, consecutively enrolled. Interventions: Dogs requiring a single pRBC transfusion were randomized into the LR or non‐LR pRBC group. Exclusion criteria included: requirement for multiple blood products, history of previous blood transfusion, and administration of anti‐inflammatory or immunosuppressive medication prior to enrollment. Measurements: Blood samples were obtained immediately prior to transfusion, then 2 and 24 hours following transfusion. Parameters measured at each time point included: PCV, WBC count, segmented and band neutrophil counts, fibrinogen, and plasma lactate and C‐reactive protein concentrations. Acute patient physiologic and laboratory evaluation fast score was calculated on admission. Results: Eleven dogs were included in the LR group and 12 in the non‐LR group; scores of illness severity were not significantly different between groups. Total WBC count was significantly higher in the non‐LR versus LR group 24 hours following pRBC transfusion, but this difference was not evident 2 hours following transfusion. No other inflammatory parameters at any time point were significantly different between LR versus non‐LR pRBC transfused dogs. Survival rates to discharge for LR and non‐LR groups were 8/11 and 9/12, respectively. Acute transfusion reactions were identified in 1/11 and 2/12 dogs in the LR and non‐LR group, respectively. All transfused blood was stored ≤12 days. Conclusions: Most markers of inflammation did not significantly increase following transfusion of LR versus non‐LR pRBCs stored ≤12 days in ill dogs. Further prospective, randomized trials are needed in clinically ill dogs to determine the benefit of prestorage leukoreduction.